Linguistic and Cultural Features of Translation Between English and Uzbek Languages - Yusup Khaytbayevich Kushakov (Scientific Trends, 2025)
This article examines the linguistic and cultural features of translation between English and Uzbek languages, focusing on semantic, grammatical, and pragmatic transformations that occur during the translation process. Special attention is given to cultural realities, idiomatic expressions, and national-specific concepts that require adaptive strategies to maintain equivalence. The study highlights the importance of cultural competence, contextual awareness, and the translator’s decision-making skills in ensuring accurate and meaningful translation. The article also provides examples of common translation challenges and outlines effective methods to overcome them.
Keywords: Translation studies, English–Uzbek translation, linguistic features, cultural adaptation, equivalence, pragmatics, translator competence.